Enhanced thermal energy transport using adiabatic block inside lid-driven cavity. (September 2016) - Biswas, Nirmalendu; Manna, Nirmal K.; Mahapatra, Pallab Sinha
Graphical abstract: Highlights: Enhanced thermal energy transport using adiabatic block in cavity is demonstrated. Optimal block sizes are identified for assisting, opposing and assisting–opposing flow. Significant heat transfer augmentation is found under opposing flow situation. Energy transport from source to sink is presented using heatlines. The impact of cavity inclination on the thermal performance is also investigated. Abstract: Most of the energy related applications are involved with heat transfer and fluid flow, and the efficient utilization of energy system is always a matter of great importance. With a simple flow geometry, the present work is devoted to report a better thermal energy transfer utilizing an adiabatic block in a sidewalls moving, differentially-heated cavity. The study demonstrates the effective role of the adiabatic block on energy transport from source to sink. The adiabatic block, depending on the situations, both favors and hinders overall heat transfer of the system. The size of the block decides the modality of thermal energy transfer. In this work, different speeds and configurations of wall motion are investigated exhaustively to assess the extent of heat transfer augmentation and the optimal block sizes. The results indicate that, up to a certain block size, the thermal energy transport of this cavity enhances. Heat transfer augmentation is remarkably high for opposing flow situation. The dynamics of energy flow from the source to the sink is presented using heatfunction that reveals the evolution of energy recirculation cells in the cavity. The presence of an adiabatic block potentially suppresses this energy recirculation. The evolved vortical flow structure in the cavity is explained using elliptical and hyperbolic points. The study is further extended to include the impact of cavity inclination on the thermal performance.